Re-distribution (condensation) of magnons in a ferromagnet under pumping - Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Last years several experiments were performed, which studied the Bose-Einstein condensation of quasi-particles, in particular, magnons in magnetically ordered systems. Recently the Bose-Einstein condensation of magnons was observed at room temperatures in a ferromagnetic film. The theory of the condensation (re-distribution) of magnons under the conditions of pumping, which explains many features of that experiment, is presented. The use of the term «Bose-Einstein condensation of magnons» is discussed.